Aplikasi Sistem Ujian Online Pada SMK Negeri 1 Gombong - Suherman Suherman; Eko Setiawan (Teknik Informatika, Universitas Pelita Bangsa, 2021)
The online exam process conducted by the State Vocational High School 1 Gombong is still done manually. Utilization of existing technology can be done with online exams with the aim of saving time, costs and energy and can also make it easier for students to obtain test results directly. In this study, an online exam information system was created using PHP as a programming language and MySQL as a database. Whereas in the zero diagram, the system is described as a work between functions that are related to each other with the flow and storage of data. Keywords: Online Exam, PHP and MySQL